Development perspectives of sports tourism in Vrnja?ka Banja - Petrović, Vladan (Hotel and Tourism Management, 2017)
Sports tourism is taking hold in the overall development of tourism in our country. Vrnja?ka Banja is considered to be one of the most developed tourist municipalities in Serbia. The tourism of Vrnja?ka Banja is constantly evolving. Owing to hosting sports competitions and the construction of new sports facilities of national importance, there has been an increase in the number of tourists in Vrnja?ka Banja. This paper presents an overview of the current state of sports infrastructure and the organisation of sports events, as well as the importance of the sports for the overall development of tourism in Vrnja?ka Banja. Based on the results of the research conducted, the guidelines for sports tourism further development can be determined.